Monitoring Keamanan Rumah Terhadap Bahaya Kebakaran Dan Untuk Efisiensi Biaya Berbasis SMS Gateway - Anshory, Izza; Charizuddin, Muhammad (J-Eltrik, 2019)
Atthidtimea lotof automationis used invariousfields that are mandatory tokmakeiteasierfor human todo allthe work. This researchisintendedtocreate a monitoring system. Thissecurity system uses arduino microcontroller asthe main controllerthatservesto improve thesignalfromthelight sensor, flame sensor,andgassensor which isthen used asoutputsignal andsenttotheactuator.Device that actas inputonthissystemare3types of sensors,theLDRsensor asa light input,flamesensoras  firedetector input,andMQ-2   gassensor that servesasagasleak detector. The programon the arduino isenabled to configure andinitialize the hardware andreceive inputsignalsfromthe 3 sensorswhichwillthebe processed undersomeconditionsto producethe desired   output.   MQ-2   and   LDR sensor test resultshowdata witha fairly  good  standard  deviation  and thisfinalresultisa homesecurity system  that  is  monitored  through SMSGateway withfastspeed notificationdelivery speedusing Telkomsel Provider.